Effect of simultaneous and sequential use of keys on the correctness of entering command strings into devices - Puka, Radosław; Łebkowski, Piotr (Technologia i Automatyzacja Montażu (Assembly Techniques and Technologies), 2019)
Controlling the operation of many devices (e.g. machine tools or assembly lines) requires that proper communication is ensured between man and the machine for the purpose of entering appropriate instructions that will control the machine operation. To this end, control panels, among other things, are used to enable the operator to control the device. Such panel may have many various forms; very often they are computer keyboards. The problem of correct entering appropriate instructions at the right moment by the operator certainly has an impact on the quality of the final product. Should the operator make a mistake, the product will not meet the desired requirements. It becomes necessary to design keyboards used as control panels in which the arrangement of characters would facilitate correct entering of instructions. One of the main issues is to define the most effective way, simultaneous or sequential, of using key while entering instructions from the control panel. The study presented in the paper describes the effect of using a combination of keys (i.e. simultaneous use of more than one key in order to enter a signal) in controlling a machine on the correctness of the signals being entered. The results presented were compared with using only the sequential pressing of keys. The study presented in the paper was conducted using a computer keyboard. This is an Open Access article distributed under the terms of the Creative Commons Attribution License CC BY 4.0 (https://creativecommons.org/licenses/by/4.0/)